1994
DOI: 10.1088/0026-1394/30/6/006
|View full text |Cite
|
Sign up to set email alerts
|

A Heterodyne Laser Interferometric Oil Manometer

Abstract: This paper describes the principle and performance of a novel manometer developed for the measurement of pressures in the range of up 1 kPa. A heterodyne interferometer using a Zeeman stabilized He-Ne laser was used to detect the displacement of oil surfaces which reflect the laser beam directly. A system of double U-tube and double interferometer was used to compensate errors caused by thermal and vibrational disturbances. The total uncertainty of the measured pressure P is estimated to be f (2,l + 0,032 P/Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Several National Metrology Institutes have developed liquid column manometers. Typically, those instruments cover the barometric pressure range, but especially in the last decades, they were also characterized as owning a measurement range starting from around 1 Pa and ending at a few kilopascals or lower [3][4][5][6].…”
Section: Liquid Column Manometrymentioning
confidence: 99%
“…Several National Metrology Institutes have developed liquid column manometers. Typically, those instruments cover the barometric pressure range, but especially in the last decades, they were also characterized as owning a measurement range starting from around 1 Pa and ending at a few kilopascals or lower [3][4][5][6].…”
Section: Liquid Column Manometrymentioning
confidence: 99%
“…The piston gauge in the atmospheric pressure range has been rapidly developing over the past few years; however, the liquid manometer is still a good choice, especially in the pressure range below 10 kPa, because it uses a different fundamental principle to realize the pressure unit. The liquid (mercury or oil) manometers in national pressure laboratories normally use one of two ways to determine the liquid column height, namely, a laser interferometer that measures the distance that the laser travels above the liquid column [1][2][3][4][5], or an ultrasonic interferometer that measures the propagating distance of ultrasound in the liquid column [6][7][8]. Because the density of mercury is well known, primary standard mercury manometers have been well developed, and obstacles to measure the mercury column heights accurately have been overcome both in laser interferometer manometers (LIMs) and ultrasonic interferometer manometers (UIMs).…”
Section: Introductionmentioning
confidence: 99%
“…NIST also developed an oil UIM with a full-scale (FS) range of 140 Pa absolute pressure, and the uncertainty for pressures above 3 Pa is [0.0015 2 + (1.8 × 10 −5 p Pa −1 ) 2 ] 1/2 Pa (k = 1) [18]. In contrast to mercury manometers, oil manometers developed by NMIs have relatively large uncertainties, for example (0.002 + 3.2 × 10 −5 p Pa −1 ) Pa (k = 1) for pressures up to 1 kPa in [1] and (0.01 + 1 × 10 −4 p Pa −1 ) Pa (k = 1) for absolute pressures from 1 Pa to 1 kPa in [4], contributed mainly by the oil density. Although mercury manometers are applied widely as primary pressure standards in NMIs, oil manometers have the advantage of low vapor pressure, low density and they are nonhazardous.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Heydemann et al 2 reported a precision mercury manometer utilizing ultrasonic interferometer to determine the heights of mercury columns. Hong et al 3 also developed an ultrasonic interferometer manometer in which the changes in length of the liquid column are determined by an ultrasonic technique.…”
Section: Introductionmentioning
confidence: 99%